Reinterpreting a complex relationship: Po Valley monasteries and royal power in the 9th-11th centuries (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
Focusing on the study of fiscal properties and their management, this contribution offers a comprehensive reassessment of the relationship between royal monasteries and the kingdom. It challenges the prevailing historiographical view that interprets the transfer of fiscal resources to monasteries as indicative of a structural and enduring weakness of royal power. The development of a dynamic perspective on the management of fiscal resources by kings—who, even when transferring full ownership to monasteries, ensured these assets retained a functional public value—is supported not only by synthesizing recent research but also through the analysis of select documentary formulae and sections of the Libellus de imperatoria potestate.
Keywords: Kingdom of Italy; royal monasteries; fiscal assets; immunity; fiscal revenues